Motivasi Belajar Siswa terhadap Mata Pelajaran Pendidikan Agama Islam di SDN Mandalawangi - Siti Nurazizah; Enoh; Asep Dudi Suhardini (Bandung Conference Series: Islamic Education, 2022)
Abstract. Islamic religious education is very important for students because, in the process of self-development and growth, students need guidance, direction, and teaching of Islamic education. In this way, students' learning motivation must be applied and improved in this subject, because in carrying out learning activities, participants must be based on having learning motivation. Therefore, to increase learning motivation, it is necessary to know and understand the factors that influence students' learning motivation to achieve the expected learning objectives. Learning motivation will move someone to do learning activities. However, entering the era of the Covid-19 pandemic the learning process was carried out boldly after the impact of the students. Based on these conditions, researchers are interested in being able to explain "Student's Learning Motivation on Islamic Studies Subjects at SDN Mandalawangi." The purpose of this study was to determine, describe, and analyze the factors that influence the learning motivation of fifth-grade students on Islamic Studies subjects at SDN Mandalawangi. The method used in this research is descriptive method with an approach and the type of research is case research. The research was conducted at SDN Mandalawangi. The data collection techniques used are observation, interviews, and documentation. The population and sample of this study were religious teachers and 5 fifth-grade students at SDN Mandalawangi. The results of this study are the factors that influence the learning motivation of fifth-grade students towards Islamic Studies subjects at SDN Mandalawangi, namely the intrinsic motivation of students in learning, extrinsic motivation of students in learning, student goals or aspirations, learning abilities, student conditions, environmental conditions, dynamic elements in learning, and teacher efforts in learning. Abstrak. Pendidikan Agama Islam sangat penting bagi peserta didik, karena dalam proses perkembangan serta pertumbuhan diri, peserta didik sangat memerlukan bimbingan, pengarahan, dan pengajaran pendidikan Islam. Dengan begitu motivasi belajar peserta didik harus diterapkan dan ditingkatkan pada mata pelajaran ini. Namun setelah masuk era pandemi Covid-19 dan proses pembelajaran dilakukan secara daring ini menimbulkan dampak kepada peserta didik. Maka dari itu untuk meningkatkan motivasi belajar tersebut harus mengetahui dan memahami faktor yang mempengaruhi motivasi belajar peserta didik sehingga tujuan belajar yang diharapkan dapat tercapai. Berdasarkan kondisi tersebut maka peneliti tertarik untuk meneliti mengenai “Motivasi Belajar Siswa Terhadap Mata Pelajaran Pendidikan Agama Islam di SDN Mandalawangi.” Tujuan dari penelitian ini adalah untuk mengetahui, mendeskripsikan, dan menganalisis faktor yang mempengaruhi motivasi belajar peserta didik kelas V terhadap mata pelajaran Pendidikan Agama Islam di SDN Mandalawangi. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif dan jenis penelitian yaitu penelitian kasus. Adapun teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Populasi dan sampel penelitian ini adalah kepala sekolah, guru agama, dan peserta didik kelas V SDN Mandalawangi. Hasil penelitian ini adalah faktor yang mempengaruhi motivasi belajar peserta didik kelas V terhadap mata pelajaran Pendidikan Agama Islam di SDN Mandalawangi yaitu motivasi intrinsik peserta didik dalam belajar, motivasi ekstrinsik peserta didik dalam belajar, cita-cita atau aspirasi siswa, kemampuan belajar, kondisi siswa, kondisi lingkungan, unsur-unsur dinamis dalam belajar, dan upaya guru dalam pembelajaran.